A Social Network Analysis of Engineering Faculty Connections: Their Impact on Faculty Student-Centered Attitudes and Practices - James A. Middleton; Stephen Krause; Eugene Judson; Lydia Ross; Robert Culbertson; Keith D. Hjelmstad; Kara L. Hjelmstad; Ying-Chih Chen (MDPI AG, 2022)
Connections among faculty who might be potential resources for diffusion of learner-centered practices across STEM departments were examined at a major research university. Specifically, the research assessed the impact of these connections on learner-centered beliefs among faculty and the implementation of learner-centered practices across the network. Participants were recruited from Physics, Chemistry, and Mathematics departments, and from departments in the College of Engineering. A snowball sampling procedure began with 21 randomly selected faculty from each department engaged in the STEM instruction of engineering students. These faculties then identified the colleagues they utilize as resources for improving their instruction. Characteristics of faculty connectedness in the network consisted of number of connections and depth of connections for both individual faculty and within and across departments. Outcome measures consisted of a survey of learner-centered attitudes and classroom observations of faculty instructional practices. The results show that faculty exhibiting more learner-centered behaviors had deeper and more extensive social networks than their peers who were more instructor-centered. The results are discussed in terms of the need for intra- and inter-departmental faculty professional development experiences that build and support collaborative organizations of faculty working together to transform early engineering experiences.